Pengaruh Risiko Kredit dan Tingkat Likuiditas Terhadap Profitabilitas Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia - Suryati, Suryati; Wiralestari, Wiralestari; Jumaili, Salman (Jurnal Akuntansi & Keuangan Unja, 2024)
This study aims to analyze the effect of credit risk and liquidity levels on the profitability of banking companies listed on the Indonesia Stock Exchange. This research is a quantitative study. The type of data used is secondary data obtained from www.idx.co.id and company websites. The population in this study consists of banking companies listed on the Indonesia Stock Exchange from 2018 to 2022. The research sample was determined using purposive sampling, resulting in a total of 105 data points that could be processed. The analysis method used is multiple linear regression analysis using SPSS version 25 software. The results of this study indicate that credit risk and liquidity levels affect profitability.